Use of Transgenic Mice as Models for Prostate Cancer Chemoprevention - A. Nguewa, P.; Calvo, A. (Current Molecular Medicine, 2010)
Prostate cancer is a long latency type of tumor that usually develops in men older than 50 years of age. Prostate epithelial neoplasia (PIN), the initial malignant lesion, progresses to invasive carcinoma over the course of years. Because of the particular features of prostate carcinogenesis, this type of tumor may represent a paradigm for cancer prevention. Several clinical trials have evaluated the effect of different compounds on prostate tumor development, including finasteride, selenium, vitamin E, and carotenes. Although some results are promising, no conclusive data have been achieved as to recommend any of these compounds as preventive agents. Results from some trials, such as SELECT, where supplementation of selenium and/or vitamin-E was used, have been rather disappointing. However, many novel chemopreventive agents that target different cancer-related pathways are being developed lately. Appropriate animal models (in particular, genetically modified mice) are being used to assess the efficacy of these novel compounds. The transgenic adenocarcinoma of the mouse prostate (TRAMP) model has been validated as an accurate model to test a variety of preventive agents. Genistein, alpha-difluoromethylornithine, toremifene, R-flurbiprofen, celecoxib, and green tea polyphenols have been shown to prevent prostate cancer development in TRAMP mice. In conclusion, new chemopreventive compounds which are effective in animal models are likely to be tested soon in clinical trials, with the final goal of reducing prostate cancer incidence in men.
Keywords: androgen therapy